Analysis of sandwich structures with corrugated and spiderweb-inspired cores for aerospace applications. (November 2022) - Tewari, K.; Pandit, M.K.; Budarapu, P.R.; Natarajan, S.
Abstract: The bending response of laminated composite sandwich structures developed for aircraft flaps is analyzed, in two parts. In the first part, the carbon fiber reinforced plastic (CFRP) and Aluminium 6061 based single-sided trapezoidal corrugated core sandwich panels are considered. The developed design is observed to withstand higher loads and exhibits higher flexural stiffness as compared to the similar corrugated geometries in the literature. The core design is iteratively modified to maximize the contact points between the core and panel in contact with the lift forces. The structure is treated as a cantilever, thus, representing the boundary conditions of aircraft flaps. The influence of ply-orientation, stacking sequences of face sheets, and panel thickness on the bending response are studied. As a result, an optimized sandwich composite structure with two times more stiffness and 40% lower stress levels as compared to the initial design is arrived. Furthermore, dynamic analysis is performed considering sinusoidally varying load along the space and time. In the second part, a novel bio-inspired spiderweb core design for the aircraft flap is developed. The stiffness of the bio-mimicked sandwich composite structures is observed to be better than the optimized corrugated core structures proposed in the first part. The influence of scaling and patterning the geometry is also investigated. The simulations are further extended to study the influence of hail impact on the sandwich structures with optimized corrugated and spiderweb cores to estimate the maximum induced stresses and peak forces. Finally, the corrugated design is replaced with the proposed spiderweb-based core design while preserving the optimal fiber orientation and ply-thickness developed in the first part. Highlights: Analysis of bending response of laminated composite sandwich structures developed for aircraft flaps, using (i) corrugated and (ii) spiderweb-inspired cores. Development of novel spiderweb-inspired core designs for the sandwich structures. Impact analysis of sandwich structures with corrugated and spiderweb-inspired cores considering real time hails impacting at medium velocities.